Opportunity for All : Promoting Growth and Inclusiveness in the Middle East and North Africa - Purfield, Catriona; Baduel, Benedicte; Finger, Harald; Ongley, Karen (Washington, D.C. : International Monetary Fund, 2018)
This publication brings together a set of IMF papers that prepared as backgrounds for the various sessions of the conference and will help put into broader dissemination channels the results of this important conference. An official IMF publication is well disseminated into academic and institutional libraries and book channels. The IMF metadata will also make the conference papers more discoverable online.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet